Entrepreneurship in Africa - Akinyoade, Akinyinka; Uche, Chibuike U. (African dynamics, 2017)
Historically, entrepreneurs have always played a central role in the development of nation states. Aside from rentier states, which depend extensively on the availability of mineral resource rents, most economically prosperous nations in the world have strong, innovative and competitive business enterprises and entrepreneurs as the bedrock of their economic development and prosperity. It was arguably because of the above historical fact that the World Bank in 1989 declared that entrepreneurs will play a central role in transforming African economies. Chapters in this book contribute to our understanding of the theory, structure and practice of entrepreneurship in diverse African countries. Case studies examined include: African multinational banks and businesses, female entrepreneurs, culture and entrepreneurship, finance and entrepreneurship and SMEs.